1989
DOI: 10.1002/1098-108x(198909)8:5<499::aid-eat2260080502>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of disordered eating among college students

Abstract: The prevalence of disordered eating among college students was assessed at the beginning and the end of the freshman year. The study aimed to identify factors related to worsening of disordered eating during the year. Questionnaires were completed by 590 males and 450 females at baseline and 546 males and 403 females at follow‐up. At baseline, the prevalence of bulimia nervosa was 3.8% for females and 0.2% for males. The prevalence of disordered eating symptoms was considerably higher. The prevalence of bulimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
118
4

Year Published

1991
1991
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(130 citation statements)
references
References 10 publications
6
118
4
Order By: Relevance
“…Longitudinal studies have demonstrated that in many cases, ED-symptoms wax and wane in severity (e.g. (35)). The high incidence rate in relation to the prevalence in the general population and the transition of symptoms among a subgroup of subjects may partly explain why only a small percentage of subjects with ED seek treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies have demonstrated that in many cases, ED-symptoms wax and wane in severity (e.g. (35)). The high incidence rate in relation to the prevalence in the general population and the transition of symptoms among a subgroup of subjects may partly explain why only a small percentage of subjects with ED seek treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, female college students appear to be particularly at risk for the development of eating disorders due to increases in independence, peer pressures, academic stress, and/or difficulty in transitioning to a new environment (Mintz & Betz, 1988;Striegel-Moore, Silberstein, Frensch, & Rodin, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Experiencing negative self-evaluation (Fairburn, Welch, Doll, Davies, & O'Connor, 1997), low self-esteem (Button, Sonuga-Barke, & Davies, 1996), and perceived ineffectiveness (Striegel-Moore et al, 1989) also have been identified as potential risk factors for eating disorders. Stice and colleagues (Stice, Akutagawa, Gaggar, & Agras, 2000;Stice, Ziemba, Margolis, & Flick, 1996) emphasized that negative affect and dietary restraint are important triggers for the development of bulimic pathology.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum possible score is 30 for Symptom Scale. A symptom score of 20 or more indicates a highly disordered eating pattern and the presence of binge eating; the medium range (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) suggests an unusual eating pattern; the low range (0-10) falls within normal limits.…”
Section: Determination Of Bedmentioning
confidence: 99%